Euterpe oleracea Mart. (Açai) Supplementation Attenuates Acute Doxorubicin-Induced Cardiotoxicity in Rats - Mathias, Lívia Maria Beraldo Simões [UNESP]; Alegre, Patricia Helena Correa [UNESP]; Dos Santos, Isadora de Oliveira Fernandes [UNESP]; Bachiega, Tatiana [UNESP]; Figueiredo, Amanda Menezes [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Fernandes, Ana Angélica [UNESP]; Bazan, Silméia Garcia Zanatti [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Azevedo, Paula Schmidt [UNESP]; Okoshi, Marina Politi [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; et al. (Cell Physiol Biochem Press, 2019)
BACKGROUND/AIMS: Doxorubicin, a chemotherapy drug used successfully for years, could induce cardiotoxicity. Euterpe oleracea Mart. (açai) is a fruit high in antioxidant properties. The aim of this study was to evaluate doxorubicin-induced cardiotoxicity prevention after açai administration. METHODS: A total of 64 male Wistar rats were allocated into 4 groups: control (C), açai (A), doxorubicin (D) and açai-doxorubicin (DA). Rats received regular chow (C and D groups) or chow supplemented with açai 5% (A and DA groups) for 4 weeks. Subsequently, rats received doxorubicin 20 mg/kg (D and DA groups) or saline (C and A groups). Euthanasia was performed 48 hours after doxorubicin injection. Left ventricular function was evaluated by echocardiography in vivo and by isolated heart study ex vivo. Oxidative stress, myocardial metabolism and nitric oxide metabolite were evaluated by spectrophotometry, MMP-2 activity by zymography and caspase-3 and Bcl-2 protein expression by Western blot. RESULTS: Doxorubicin induced decreases in body weight, food and water ingestion. We observed decreases in left ventricular fractional shortening in rats treated with doxorubicin. Additionally, the same rats showed lower +dP/dt and -dP/dt during isolated heart study than those who did not receive doxorubicin. Doxorubicin injection increased caspase-3 protein expression, myocardium lipid hydroperoxide concentration, MMP-2 activity, phosphofructokinase and lactate dehydrogenase activity, and decreased β-hydroxyacyl-CoA dehydrogenase, pyruvate dehydrogenase, citrate synthase, complex I, complex II and ATP synthase activity in myocardium. Açai supplementation improved left ventricular fractional shortening, decreased myocardium lipid hydroperoxide concentration, MMP-2 activity, and improved β-hydroxyacyl-CoA dehydrogenase, phosphofructokinase, citrate synthase, complex II and ATP synthase enzymatic activities. We did not observe differences in nitric oxide metabolite concentrations between groups. CONCLUSION: Doxorubicin induced left ventricular dysfunction, increases in oxidative stress, changes in myocardium metabolism and MMP-2 activation. Açai supplementation was able to prevent these alterations.
Keywords: Apoptosis; Cardiac function; Matrix metalloproteinase-2; Oxidative stress